Urgensi Berpikir Kritis melalui Pedagogi Reflektif dalam Pembelajaran Keterampilan Berbahasa Siswa Kelas 1 SD - Theresia Avila Clarita Oktavi; Yuliana Setiyaningsih; Galih Kusumo; R. Kunjana Rahardi (Institut Agama Islam Negeri Curup, 2026)
Abstrak. Penelitian ini berangkat dari persoalan rendahnya kemampuan berpikir kritis siswa sekolah dasar, khususnya pada pembelajaran keterampilan berbahasa yang masih bersifat konvensional dan berpusat pada guru. Tujuan penelitian ini ialah mendeskripsikan kondisi aktual pembelajaran keterampilan berbahasa siswa kelas 1 SD serta mengidentifikasi aspek berpikir kritis yang dapat dikembangkan melalui penerapan pedagogi reflektif. Penelitian menggunakan pendekatan campuran (mixed methods) dengan model pengembangan ADDIE pada tahap analisis, melalui penyebaran angket dan wawancara mendalam kepada guru kelas 1 SD. Hasil penelitian menunjukkan bahwa pembelajaran bahasa masih menekankan aspek teknis membaca dan menulis tanpa aktivitas reflektif dan multimodal yang dapat menstimulasi daya nalar siswa. Guru juga menunjukkan kebutuhan tinggi terhadap modul pembelajaran berbasis pedagogi reflektif yang memuat kegiatan refleksi sederhana dan menyenangkan. Temuan ini menegaskan pentingnya pengembangan model pembelajaran yang mengintegrasikan refleksi dan multimodalitas untuk memperkuat kemampuan berpikir kritis sejak dini. Penelitian ini diharapkan menjadi dasar bagi pengembangan modul pembelajaran keterampilan berbahasa berbasis pedagogi reflektif yang lebih kontekstual dan aplikatif, serta membuka peluang bagi penelitian lanjutan tentang implementasinya di berbagai jenjang sekolah dasar. Kata Kunci: berpikir kritis, pedagogi reflektif, keterampilan berbahasa, sekolah dasar Abstract. This study is motivated by the low level of critical thinking skills among elementary school students, particularly in language skills instruction that remains conventional and teacher-centered. The study aims to describe the actual conditions of language skills learning in Grade 1 elementary classrooms and to identify aspects of critical thinking that can be developed through the implementation of reflective pedagogy. The research employed a mixed-methods approach within the framework of the ADDIE development model, focusing on the analysis stage. Quantitative data were collected through questionnaires administered to Grade 1 elementary school teachers to map learning conditions and instructional module needs, while qualitative data were obtained through in-depth interviews. Quantitative data were analyzed descriptively, whereas qualitative data were analyzed thematically. The findings indicate that language skills learning still emphasizes technical aspects of reading and writing and has not yet integrated reflective and multimodal activities that can stimulate students’ reasoning abilities. Teachers also expressed a high need for instructional modules based on reflective pedagogy that incorporate simple and engaging reflective activities. The findings further reveal that language skills instruction in Grade 1 elementary classrooms has not sufficiently developed critical thinking skills, particularly students’ abilities to observe, articulate simple reasoning, and reflect on their understanding. Therefore, the development of instructional models that integrate reflection and multimodality is necessary to strengthen students’ critical thinking skills from an early age. This study is expected to serve as a foundation for the development of more contextual and applicable reflective pedagogy-based language skills modules and to open opportunities for further research on their implementation across various levels of elementary education. Keywords: critical thinking, reflective pedagogy, language skills, elementary school